2015
DOI: 10.1007/s00104-015-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymphknotendissektion nach primärer Chirurgie und neoadjuvanter Radiochemotherapie des Rektumkarzinoms

Abstract: In this trial the number of identified lymph nodes suggests that the quality of surgery and histopathological work-up were adequate compared to the standards defined by national guidelines. Neoadjuvant radiochemotherapy led to a reduced lymph node yield compared to surgery without pretreatment; however, this did not influence the rate of lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We also found that patients in the NACRT group had significantly fewer metastatic lymph nodes than patients in the no-NACRT group. Consensus in the literature varies in terms of the relationship between the number of metastatic lymph nodes and prognosis [3,4,25]. In our study, patients who underwent NACRT tended to have a better (although not significantly so) 5-year DFS (80.3% versus 73.2%) (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…We also found that patients in the NACRT group had significantly fewer metastatic lymph nodes than patients in the no-NACRT group. Consensus in the literature varies in terms of the relationship between the number of metastatic lymph nodes and prognosis [3,4,25]. In our study, patients who underwent NACRT tended to have a better (although not significantly so) 5-year DFS (80.3% versus 73.2%) (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…The MERCURY study showed that lymph node involvement is not an independent predictor of local recurrence, and using CRM was recommended for evaluating neoadjuvant therapy (82). In this case, clinical lymph node assessment for rectal cancer may only play a secondary role in guiding future treatment decisions (83,84). This study has some limitations.…”
Section: Discussionmentioning
confidence: 91%